2017
DOI: 10.1172/jci.insight.89044
|View full text |Cite
|
Sign up to set email alerts
|

Switching harmful visceral fat to beneficial energy combustion improves metabolic dysfunctions

Abstract: Visceral fat is considered the genuine and harmful white adipose tissue (WAT) that is associated to development of metabolic disorders, cardiovascular disease, and cancer. Here, we present a new concept to turn the harmful visceral fat into a beneficial energy consumption depot, which is beneficial for improvement of metabolic dysfunctions in obese mice. We show that low temperature–dependent browning of visceral fat caused decreased adipose weight, total body weight, and body mass index, despite increased foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…Similar gene regulation, involved in thermogenic response and mitochondrial oxidation, was found in rats treated with Lep -expressing adenovirus (Zhou, Wang, Higa, Newgard & Unger 1999). Cao and co-workers proposed that this gene regulation can effectively reduce iAb fat depots (Yang, Sui, Zhang, Dong, Lim, Seki, Guo, Fischer, Lu, Zhang et al 2017). Both studies are in agreement with the proposed function of EREG as an upstream regulator of LEP secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Similar gene regulation, involved in thermogenic response and mitochondrial oxidation, was found in rats treated with Lep -expressing adenovirus (Zhou, Wang, Higa, Newgard & Unger 1999). Cao and co-workers proposed that this gene regulation can effectively reduce iAb fat depots (Yang, Sui, Zhang, Dong, Lim, Seki, Guo, Fischer, Lu, Zhang et al 2017). Both studies are in agreement with the proposed function of EREG as an upstream regulator of LEP secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the browning ability differences, do adipose depots contribute to CAC differently? It has been reported that visceral fat may switch its phenotype for browning under certain stimulations (Yang et al, 2017), though the switching mechanism is still not well understood. This interesting question warrants further investigation and may improve our understanding of the mechanism of browning-conferred CAC.…”
Section: Browning In Cacmentioning
confidence: 99%
“…In the present study, because the total VAT mass was ~3.0-fold higher than the SAT mass, the improvement of VAT function, such as increased WAT browning, could explain the improvement of whole body glucose metabolism in diabetic GK rats after IT surgery. Similarly, it was reported by Yang et al that browning of VAT could improve global glucose and lipid metabolism, insulin sensitivity and hepatic steatosis in HFD-induced obese mice (Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 56%